Zero valent zinc regulates adipocyte differentiation through calpain family protein and peroxisome proliferator-activated receptor gamma signaling in mouse 3T3-L1 cells. (February 2021) - Ramalingam, Vaikundamoorthy; Hwang, Inho
Graphical abstract: Highlights: The hexagonal structure of ZVZ nanoparticles was prepared using chemical approach. ZVZ nanoparticles was spherical in shape and well dispersed in nature. ZVZ nanoparticles showed less cytotoxic activity against 3T3-L1 cells. ZVZ nanoparticles enhances the significant morphological changes from preadipocytes to mature adipocytes. ZVZ nanoparticles increase ROS generation which regulates key adipogenic marker genes during cell differentiation. Abstract: In the present study, the zero valent zinc (ZVZ) was used in the field of tissue regeneration engineering by inducing the preadipocytes into mature adipocytes in mouse 3T3-L1 cells. Initially, the ZVZ nanoparticles was synthesized using chemical reduction method and confirmed by EDS spectrum analysis which showed the presence of zinc ion without any impurities. The XRD and Raman analysis showed the characteristic peaks of zinc with hexagonal structure and the strong phonon band attributed to ZVZ, respectively. The microscopic analysis showed the ZVZ nanoparticles are well dispersed with spherical shape and the size was found to between 85−95 nm. The in vitro cytotoxic activity of ZVZ against 3T3-L1 showed less toxicity in higher concentration and the results were compared with standard adipogenic stimulant dexamethasone. The oil red O staining assay morphologically confirmed the ZVZ induces adipogenesis in 3T3-L1 as well as increase the lipid accumulation during treatment with ZVZ. Moreover, the ZVZ upregulates the expression of adipogenic marker genes such as PPARγ, FABP4 and the calpain family protein during differentiation of preadipocytes into mature adipocytes. Together, the ZVZ regulates the differentiation in 3T3-L1 cells through PPARγ and calpain signaling pathway deciphers the role of ZVZ in tissue regeneration engineering.